Analysis of Arabidopsis floral transcriptome: detection of new florally expressed genes and expansion of Brassicaceae-specific gene families - Zhang, Liangsheng; Wang, Lei; Yang, Yulin; Cui, Jie; Chang, Fang; Wang, Yingxiang; Ma, Hong (Frontiers in Plant Science, 2015)
The flower is essential for sexual reproduction of flowering plants and has been extensively studied. However, it is still not clear how many genes are expressed in the flower. Here, we performed RNA-seq analysis as a highly sensitive approach to investigate the Arabidopsis floral transcriptome at three developmental stages. We provide evidence that at least 23, 961 genes are active in the Arabidopsis flower, including 8,512 genes that have not been reported as florally expressed previously. We compared gene expression at different stages and found that many genes encoding transcription factors are preferentially expressed in early flower development. Other genes with expression at distinct developmental stages included DUF577 in meiotic cells and DUF220, DUF1216 and Oleosin in stage 12 flowers. DUF1216 and DUF577 are Brassicaceae specific, and together with other families experienced expansion within the Brassicaceae lineage, suggesting novel/greater roles in Brassicaceae floral development than other plants. The large dataset from this study can serve as a resource for expression analysis of genes involved in flower development in Arabidopsis and for comparison with other species. Together, this work provides clues regarding molecular networks underlying flower development.